2006
DOI: 10.1038/sj.bdj.4813371
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of photo-activated disinfection in endodontics (An in vivo study)

Abstract: Objective To determine the microbiological effect of photoactivated disinfection (PAD) as an adjunct to normal root canal disinfection in vivo. Design A randomised trial carried out in general dental practice. Subjects and methods Patients presenting with symptoms of irreversible pulpitis or periradicular periodontitis requiring endodontic therapy were selected at random. A microbiological sample of the canal was taken on accessing the canal, after conventional endodontic therapy, and finally after the PAD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 18 publications
2
136
0
18
Order By: Relevance
“…This follows previous work in which it was established that the use of hypochlorite was successful in eliminating culturable bacteria from the walls of the canals in only 76% of the cases treated. 23 Citric acid is a well documented chelating agent and had been used frequently in dentistry as a means of smear removal and breakdown of any biofilm layer. Its use, prior to a disinfecting agent, as a biofilm disrupter would facilitate the passage of the disinfecting solution into both the lateral canals and open dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This follows previous work in which it was established that the use of hypochlorite was successful in eliminating culturable bacteria from the walls of the canals in only 76% of the cases treated. 23 Citric acid is a well documented chelating agent and had been used frequently in dentistry as a means of smear removal and breakdown of any biofilm layer. Its use, prior to a disinfecting agent, as a biofilm disrupter would facilitate the passage of the disinfecting solution into both the lateral canals and open dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a novel disinfecting system has been tested as an adjunct to conventional root canal therapy using sodium hypochlorite and citric acid as root canal cleaners. 23 The PAD process uses a photosensitiser, specifically Tolonium chloride solution (TC) (a pharmaceutical grade of Toluidine Blue O), and light of a specific wavelength [633±2nm]. This may be used in conjunction with a biofilm/smear remover such as citric acid.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
See 1 more Smart Citation
“…14 Several studies have shown that oral bacteria are sensitive to photodynamic therapy (PDT). 15,16 In recent years, in vitro [17][18][19][20][21][22][23][24][25][26] and in vivo [27][28][29] studies have been performed to investigate the antibacterial effect of the PDT on the microorganisms in root canal. Most of these studies have focused on the PDT capability as a complementary technique besides the conventional endodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial infection plays an important role in the development of dental pulp necrosis and formation of periapical lesions (1). It is well established that the eradication of intracanal bacteria is difficult, and current endodontic techniques are unable to consistently disinfect the the root canal systems (2). Accepted treatment procedures to eliminate the infection include root canal debridement and mechanical shaping or smoothing (3), irrigation with disinfectant agents, such as sodium hypochlorite or hydrogen peroxide, application of an interappointment intracanal dressing containing an antimicrobial agent and finally, root canal sealing (4).…”
Section: Introductionmentioning
confidence: 99%